PENGGUNAAN JENAZAH UNTUK KEPENTINGAN PENELITIAN ILMIAH PERSPEKTIF FAZLUR RAHMAN - Abdurahman Syayuthi (Journal Analytica Islamica, 2020)
Abstract: The development of science and technology that is currently going on in the field of medical transplant surgery or the use of dead bodies for the purposes of scientific research. In this case the use of dead bodies that was one of the findings of the modern medical technology with the methods in the form of tissue or organs removal of the body from one place to another to replace organs that are not healthy and not functioning properly. It means that this technological advancement in the field of medical studies helps many parties, but the attempt to use of dead bodies in this study also clearly raises several problems that have an impact on morality. This study aimed to find out how the concept of Fazlur Rahman’s methodology and how the law views about the use of dead bodies for scientific research. This study used methodology of normative juridical approaches that are directly related to library research and qualitative method gathered data collection from primary, secondary legal sources, and documents. The results of this study mentioned that Fazlur Rahman's methodology using the "double movement" theory approach, from the present time is returned when the holy Al-Quran revealed to find the authenticity of the text and returned to the present is seen in historical theory and hermeneutics and the message of moral values contained by using Islamic legal sources namely Al-Quran, Sunnah, Ijtihad ', ans Ijma'. As for the law on the issues of the use of dead bodies for scientific purposes according to Fazlur Rahman, with a note that the dead body has a purpose on its usefulness, then the law is permitted to be carried out if in a situation involving the benefit of the people and Fazlur Rahman supports the development of science on the condition that there are objectives related to humanity and emphasizes for every Muslim to act by not staying silent on the problems of life. So that, the ideas of Fazlur Rahman are always related to functions and uses.Keywords: the use of dead bodies, scientific research, Fazlur Rahman’s